PERBANDINGAN HASIL RIASAN MENGGUNAKAN TEKNIK AIRBRUSH DAN TEKNIK MANUAL PADA RIAS PENGANTIN GAUN PANJANG - Chindi Syuhkrina; Murni Astuti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: The problem in this study arises from the demands of long-gown bridal makeup, which requires a smooth, even, natural, and long-lasting complexion, while the application of airbrush and manual (sponge) techniques in practice still shows inconsistent results. Although the airbrush technique is theoretically considered modern, hygienic, and effective, observations indicate that students of the Makeup and Beauty Study Program are more skilled in using the sponge technique, resulting in the effectiveness of both techniques not being objectively evaluated. This study aims to analyze the differences in makeup results between the airbrush and sponge techniques based on indicators of smoothness, durability, evenness, and panelist preference levels. The research employed a One Shot Case Study design with six samples with oily facial skin, evaluated by seven panelists. The hypothesis test results showed a significant difference only in the evenness indicator, with the sponge technique demonstrating superiority. Overall, the sponge technique proved to be more optimal for long-gown bridal makeup, particularly on oily skin. Keywords: Airbrush, Makeup Results, Bridal Makeup, Sponge.